An Amazing Result Involving Contiguous Relation : A Comutational Approach (Global Journal of Science Frontier Research, 2014)
The main aim of the present paper is to evaluate an amazing summation formula involving recurrence relation of Gamma function and contiguous relation.
Keywords: gauss second summation theorem; recurrence relation; prudnikov